Teamwork skills (New York : Ferguson, 2009)
A guide to developing teamwork skills, particularly in the workplace
The corporate dream team -- Become people smart -- Understanding team culture -- World cup teams -- Team conflicts and other concerns -- Team goal setting and negotiating -- Avoid team-killing behaviors.
Includes bibliographical references (p. 159-163) and index
Keywords: Teams in the workplace -- Juvenile literature; Teams in the workplace; Vocational guidance